ASSESSMENT OF THE PROPORTIONAL CONTRIBUTION OF THE CONSUMER TO THE VOLTAGE UNBALANCE NEGATIVE SEQUENCE NETWORKS WITH ISOLATED NEUTRAL - Dmitrii Kostyukov; Anton Petrov; Anna Kushch (Вестник Северо-Кавказского федерального университета)
The article presents a technique for estimating the consumer's contribution to the unbalance level of the negative sequence voltage at the point of common connection. The results of a computational experiment that determine the possibility of using the level of the active component of the distortion power as a criterion of estimation are presented. It is shown that information about the symmetrical componenthe consumers' currents and voltages at the point of common connection is minimal enough to estimatelevel of the consumer's contribution to the voltage asymmetry.